A Novel Fully Differential Second Generation Current Conveyor and Its Application as a Very High CMRR Instrumentation Amplifier - Ahmadi, Soma; Azhari, Seyed Javad (Emerging Science Journal, 2018)
This paper aims to introduce a novel Fully Differential second generation Current Conveyor (FDCCII) and its application to design a novel Low Power (LP), very high CMRR, and wide bandwidth (BW) Current Mode Instrumentation Amplifier (CMIA). In the proposed application, CMRR, as the most important feature, has been greatly improved by using both common mode feed forward (CMFF) and common mode feedback (CMFB) techniques, which are verified by a perfect circuit analysis. As another unique quality, it neither needs well-matched active blocks nor matched resistors but inherently improves CMRR, BW, and power consumption hence gains an excellent matchless choice for integration. The FDCCII has been designed using 0.18 um TSMC CMOS Technology with ±1.2 V supply voltages. The simulation of the proposed FDCCII and CMIA have been done in HSPICE LEVEL 49. Simulation results for the proposed CMIA are as follow: Voltage CMRR of 216 dB, voltage CMRR BW of 300 Hz. Intrinsic resistance of X-terminals is only 45 Ω and the power dissipation is 383.4 μW. Most favourably, it shows a constant differential voltage gain BW of 18.1 MHz for variable gains (here ranging from 0 dB to 45.7 dB for example) removing the bottleneck of constant gain-BW product of Voltage mode circuits.